Hypoxia within the glioblastoma tumor microenvironment: a master saboteur of novel treatments - Feldman, Lisa (Frontiers in Immunology, 2024)
Glioblastoma (GBM) tumors are the most aggressive primary brain tumors in adults that, despite maximum treatment, carry a dismal prognosis. GBM tumors exhibit tissue hypoxia, which promotes tumor aggressiveness and maintenance of glioma stem cells and creates an overall immunosuppressive landscape. This article reviews how hypoxic conditions overlap with inflammatory responses, favoring the proliferation of immunosuppressive cells and inhibiting cytotoxic T cell development. Immunotherapies, including vaccines, immune checkpoint inhibitors, and CAR-T cell therapy, represent promising avenues for GBM treatment. However, challenges such as tumor heterogeneity, immunosuppressive TME, and BBB restrictiveness hinder their effectiveness. Strategies to address these challenges, including combination therapies and targeting hypoxia, are actively being explored to improve outcomes for GBM patients. Targeting hypoxia in combination with immunotherapy represents a potential strategy to enhance treatment efficacy.